Integrating Agriculture and Health Research for Development: LCIRAH as an Interdisciplinary Programme to Address a Global Challenge. Issue 4 (3rd April 2018) - Waage, Jeff; Cornelsen, Laura; Dangour, Alan D.; Green, Rosemary; Häsler, Barbara; Hull, Elizabeth; Johnston, Deborah; Kadiyala, Suneetha; Lock, Karen; Shankar, Bhavani; Smith, Richard D.; Walls, Helen L.
Abstract: The multiple burdens of persistent undernutrition and micronutrient deficiencies, along with the rapidly growing rates of overweight, obesity, and associated chronic diseases, are major challenges globally. The role of agriculture and the food system in meeting these challenges is very poorly understood. Achieving food security and addressing malnutrition in all its forms, a Sustainable Development Goal, requires an understanding of how changing food systems affect health outcomes and the development of new tools to design and evaluate interventions. An interinstitutional programme to address this interdisciplinary research challenge is described. Over the past seven years, the Leverhulme Centre for Integrative Research on Agriculture and Health has built a portfolio of successful and innovative research, trained a new cadre of interdisciplinary researchers in "Agri‐Health, " and built an international research community with a particular focus on strengthening research capacity in low‐ and middle‐income countries. The evolution of this programme is described, and key factors contributing to its success are discussed that may be of general value in designing interdisciplinary research programmes directed at supporting global development goals. Abstract : The Leverhulme Centre for Integrative Research on Agriculture and Health (LCIRAH) has built a portfolio of innovative interdisciplinary research projects addressing the relationship between agriculture, nutrition, and health in low‐ and middle‐income countries. This paper describes how LCIRAH developed this new area of research and training and created a global interdisciplinary research community, and shares lessons learned from this process.